Walking the tightrope: a balanced discussion of the benefits and harms of extended duration anticoagulation for venous thrombo-embolism. (19th January 2023) - Piazza, Gregory
Graphical Abstract: Graphical Abstract The balance of shared decision-making in determining the optimal duration of anticoagulation after venous thrombo-embolism.